Implementación de la plataforma moodle, como herramienta pedagógica para mejorar el aprendizaje de los estudiantes de básica superior de la Unidad Educativa Miguel Ángel - Marlo Daniel, Sañay Moina (2021)
Abstract This research called "Implementation of the MOODLE platform, as a pedagogical tool to improve the learning of the students of Upper Basic of the Educational Unit (EU onwards)" Miguel Ángel Zambrano ", with the objective to implement the MOODLE platform as a pedagogical tool in the students from the aforementioned institution. Where it could be evidenced that it presents a series of problematic situations associated with virtualization and that they do not use a platform that allows students to consolidate learning. All this caused by technological gaps and that not all students have been able to use technology, because they do not have internet access. This situation brings as consequences that students do not access virtual classes, affecting school performance and development that they must reach an academic and personal level. From the consideration of the constructivist and connectivist theory, as well as the elaboration of the body of concepts in accordance with the proposed objectives. The methodology used through a quantitative approach, with pre-experimental design and application level, with the implementation of the MOODLE platform, the type of research is field, applied in the "Miguel Ángel Zambrano" Educational Unit, having a population composed of 64 students belonging to the aforementioned institution; while the technique used for data collection was the survey and the instrument used a questionnaire. The data were analyzed using the SPSS program and the results allowed to establish that there is significance between the implementation of the platform and the learning of the students, also showing the need for the training of teachers in the use of the MOODLE platform and in the use of the instructional design ADDIE. Keywords: B-LEARNING, LEARNING MANAGEMENT SYSTEMS, METHODOLOGY. Reviewed by: Lic. Marlene de la Caridad Mena Viamonte ENGLISH PROFESSOR c.c. 1758391393